Combined effect of sodium selenite and docetaxel on PC3 metastatic prostate cancer cell line - Freitas, Mariana (2011)
Docetaxel and sodium selenite are well known for their anticancer properties. While resistance to docetaxel remains an obstacle in prostate cancer chemotherapy, sodium selenite, has been exploited as a new therapeutic approach. Currently, development of therapies affecting a multitude of cell targets, have been proposed as a strategy to overcome drug resistance. This association may reduce systemic toxicity counteracting a wide range of side effects. Here we report the effect of docetaxel and sodium selenite combination on the PC3 prostate cancer cell line, derived from bone metastasis. Therefore we evaluate cell growth, cell cycle progression, viability, mitochondria membrane potential, cytochrome C, Bax/Bcl2 ratio, caspase-3 expression and reactive oxygen species production. Our results suggest that sodium selenite and docetaxel combination have a synergistic effect on cell growth inhibition (67%) compared with docetaxel (22%) and sodium selenite (24%) alone. This combination also significantly induced cell death, mainly by late apoptosis vs necrosis, which is correlated with mitochondria membrane potential depletion. On the other hand, cytochrome C, Bax/Bcl2 ratio and caspase-3, known as proapoptotic factors, significantly increased in the presence of sodium selenite alone, but not in the presence of docetaxel in monotherapy or in combination with sodium selenite. These findings suggest that docetaxel and sodium selenite combination may be more effective on prostate cancer treatment than docetaxel alone warranting further evaluation of this combination in prostate cancer therapeutic approach.